The Design Thinking Method and Information Science research - Apocalypse, Simão Marcos [UNESP]; Jorente, Maria José Vicentini [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2022)
Objective: The present article aimed, in a general way, to investigate the Design Thinking method, its phases and techniques and, in a specific way, to describe the method; explore its use in Information Science research; and to identify the potential of the method in the research developed in the area. Methods: This article is qualitative in nature and has a theoretical and exploratory approach. To reach the outlined objectives, we chose to use the Systematic Literature Review, aiming to identify the scientific productions on the Design Thinking Method in Information Science. Results: The survey of research published in the field of Information Science that used the Design Thinking method showed that the use of Design Thinking in the area is emerging. On the other hand, the detailed analysis of publications and their approaches showed that although research use Design Thinking as a method, the in-depth understanding of the phases, techniques and procedures still configures a theoretical gap to be filled in the field of Information Science. Conclusions: the application of the Design Thinking method in studies undertaken in Information Science, punctually with the new demands facing technological development, demonstrates potential contributions to the understanding of complex problems and to the exploration of innovative creative solutions.
O MÉTODO DESIGN THINKING E A PESQUISA EM CIÊNCIA DA INFORMAÇÃO
Keywords: Design Thinking; Information Science; Scientific Methodology